Empowering Freshmen through Development Course in Developing Students’ Speaking Skills at Poltekkes Kementerian Kesehatan Makassar - Mubarak, Ismail; Amin, Ummul Khair (IJOCSE: Indonesian Journal of Community Services, 2024)
Community Service Engagement initiatives through collaboration to empower student in dealing with the current era of globalization at Medical Laboratory Technologist Department, Health Polytechnic of the Ministry of Health Makassar and English Education Studies Program at Alauddin State Islamic University of Makassar in the program called “Development Course”. The program that aims to develop freshmen personal and professional skill. The community services focus on English Language Learning, in developing freshmen speaking skill to prepare them faced the global challenges. In this program, freshmen learn English to shape their speaking skill that would Improve their English language skills. The method carried out through community service Initiatives in teaching with Communicative Language Teaching (CLT) to Increase students’ communicative skill. The participants of this program are freshmen with approximately 40 students. Several materials delivered by the presenter that encourage participant to actively engage in the learning process, the activities build in fun situation. Throughout the community service initiatives, students acquire new knowledge that empower them in facing global challenges as well as college life.